Measuring Cerebrovascular Reactivity: The Dynamic Response to a Step Hypercapnic Stimulus. Issue 11 (November 2015) - Poublanc, Julien; Crawley, Adrian P; Sobczyk, Olivia; Montandon, Gaspard; Sam, Kevin; Mandell, Daniel M; Dufort, Paul; Venkatraghavan, Lashmikumar; Duffin, James; Mikulis, David J; Fisher, Joseph A
We define cerebral vascular reactivity (CVR) as the ratio of the change in blood oxygen level-dependent (BOLD) magnetic resonance imaging (MRI) signal (S) to an increase in blood partial pressure of CO2 (PCO2 ): % Δ S/Δ PCO2 mm Hg. Our aim was to further characterize CVR into dynamic and static components and then study 46 healthy subjects collated into a reference atlas and 20 patients with unilateral carotid artery stenosis. We applied an abrupt boxcar change in PCO2 and monitored S. We convolved the PCO2 with a set of first-order exponential functions whose time constant τ was increased in 2-second intervals between 2 and 100 seconds. The τ corresponding to the best fit between S and the convolved PCO2 was used to score the speed of response. Additionally, the slope of the regression between S and the convolved PCO2 represents the steady-state CVR (ssCVR). We found that both prolongations of τ and reductions in ssCVR (compared with the reference atlas) were associated with the reductions in CVR on the side of the lesion. τ and ssCVR are respectively the dynamic and static components of measured CVR.